PENGARUH PERAN KEPALA SEKOLAH, LINGKUNGAN KERJA, DAN KOMITMEN GURU TERHADAP DISIPLIN GURU SEKOLAH DASAR DI UPT PPD KECAMATAN IMOGIRI, BANTUL (JURNAL ILMIAH TUT WURI HANDAYANI, 2015)
The purpose of this study was to determine the extent of the effect in parallel the principal role, the work environment and commitment of teachers together to work discipline elementary school teacher in UPT-PPD Imogiri.The technique of determining the number of samples used in this study refer to the table base nomogram Harry King with an error rate of 5% has a confidence level of 95 % of the population. Total sample was 157 people. The technique of collecting data using questionnaires. The analysis used is multiple regression analysis and partial correlation.The results of the study concluded that the principal's role, work environment and commitment of teachers together a positive significant influence on the discipline of elementary school teachers working in UPT-PPD Imogiri. If the principal role, the work environment and the commitment of teachers increased labor discipline teachers also increased, and vice versa the principal role, the work environment and commitment to the discipline teacher working decreasing teacher will also go down.Â